The Analysis Of Creative Writing Teaching Through Story Book Reading For The First Grade Students Of Tunas Muda International School - Agus, Jaclyn Ryani; Winiharti, Menik (Bina Nusantara University, 2011)
One method to support the success of teaching of writing skills is using story books. It has many kinds of benefits that provides the students more creative and challenging texts that require personal exploration, easier understanding of information which are commonly hard to comprehend and remember, and easier illustration in making connection among various elements and concepts being taught. This research deals with teaching creative writing through story book reading, and it is aimed at finding whether this method is beneficial or not in increasing creativity in writing. The study is carried out using a pre-test and post-test design to 14 students from the first grade. Between the two tests, the students were provided with basic knowledge of creative writing. The data of the research were the scores of the pre-test and post-test compared and analyzed based on the rubric of ideas, organization, word choice, sentence fluency, and conventions. The pre-test result shows that 29% of the students achieve the standard of achievement. After the creative writing process, the post-test result indicates that 93% of the students achieve the standard of student achievement in creative writing.